2018
DOI: 10.4028/www.scientific.net/ssp.284.1163
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Metastable Austenite to Increase the Wear Resistance of Steels of the Pearlite Class

Abstract: The wide application of steel 110G13L for armor plates in mills and crushers makes it urgent to search for alternative materials with close or sufficient operational stability in conditions of shock abrasive wear. A promising path in this direction is the replacement of steel 110G13L with high-carbon pearlitic steels. The aim of this work is a comparative study of the relationship between the structure formed in the heat treatment process of the low-alloyed pearlite steels 70X2GSML and 150HNML and their abrasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…It is shown that the curves for both steels and ball diameters have an increasing dependence on the degree of plastic strain similar to the hardening curves for plastic strain compression. This indicates an increase in the strain degree at the bottom of the indentation cups as the indenter load increases [3,9,10].…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…It is shown that the curves for both steels and ball diameters have an increasing dependence on the degree of plastic strain similar to the hardening curves for plastic strain compression. This indicates an increase in the strain degree at the bottom of the indentation cups as the indenter load increases [3,9,10].…”
Section: Resultsmentioning
confidence: 91%
“…This method was used for comparative evaluation of two wear-resistant steels on the basis of stable high-manganese austenite-110G13L and metastable austenitic manganese steel -110G6L. Mechanisms of strain hardening of these steels have been investigated earlier [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The hardness impresses show ferromagneticity when measured with a ferrometer at all loads and diameters on steel samples 60G9Kh4L, while similar hardness impresses are non-magnetic on 110G13L steel samples. This fact indicates the appearance of α-martensite upon indentation of spherical indenters into the surface of metastable austenitic steel 60G9Kh4L, in which the transformation under loading proceeds according to the scheme γ → ε → α [1] and indicates the stability of austenite of 110G13L steel under loading.…”
Section: Resultsmentioning
confidence: 98%
“…This method was used for comparative evaluation of two wear-resistant steels on the basis of stable high-manganese austenite-110G13L and metastable austenitic chromium-manganese steel -60G9Kh4L. Mechanisms of strain hardening of these steels have been investigated earlier [1].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of disperse crystals of martensite deformation by the shear mechanism is accompanied by the relaxation of microstrains at the moment of transformation (the micro-triplet effect). As a result of γ → α transformation, the high strength of the working surfaces of steels and their operability in abrasive wear conditions are provided [6].…”
Section: Research Resultsmentioning
confidence: 99%